Structural Analysis of a Water Molecule and Its Physical Properties (Proceedings of Faculty of Civil Engineering, 2020)
Water (H2O) is a polar inorganic compound that is almost colorless at room temperature. It is by far the most common substance on Earth and among very few substances, which exists on the Earth’s surface as a solid, liquid and gaseous substance. As a relatively simple chemical compound, it has been described as a “universal solvent” or “solvent of life”. It is also the third most common molecule in the Universe. Water molecules form strong polar hydrogen bonds with each other, which, in turn, define its specific physical and chemical properties. Hydrogen bonds are responsible for many unique properties such as the anomaly of water (the fact that its solid form, the ice, is less dense than the liquid form), a relatively high boiling point (100 °C) and a high heat capacity. Water is an amphoteric molecule, which means that it can show properties of both acids and alkaline solutions, depending on the chemical environment. In this paper, a structural analysis of a water molecule and its most important physical properties was carried out in detail with regard to its anomalies. One of the important physical properties of a liquid that strongly influences our environment is the low density of ice in relation to the liquid phase of water, and the phenomenon of the negative expansion coefficient of cold water. This work also describes the solutions of the nuclear Schrödinger equations, which provide information about the internal motions (vibrations and rotations) of a water molecule.
Keywords: structure of the water molecule; physical properties of water; thermal properties of water; dimer; Schrödinger equation; P-V-T diagram